ACCOUNTING TREATMENT OF HISTORICAL ASSETS BASED ON INTERPRETIVIST PARADIGM - Hendy Satria; Novi Chandra Saputra; Juhli Edi S; M Isa Alamsayahbana; Fauzi Fauzi (PENANOMICS: International Journal of Economics, 2022)
This study aims to determine the accounting application for the Department of Revenue and Financial Management and Regional Assets of the Tanjungpinang City Government in the recognition, assessment, presentation and disclosure of the Grand Mosque of Sultan Riau Penyengat in financial statements. This research is expected to provide clearer information regarding historical aset accounting standards. This study uses a qualitative case study approach. Data were collected through primary data. through respondent interviews and secondary data from supporting documents. The results of this study indicate that the recognition of historical asets in this mosque has no "value" because it is not easy to determine the age or value of these historic asets. The practice of accounting for historic asets at the Grand Mosque of Sultan Riau Penyengat has met the standards set by the government, because there is an assessment and presentation of historical asets has been carried out in the notes to the financial statements.